A form-finding method for spatial arch bridges based on inverse hanging method. (December 2022) - Zhao, Zhongwei; Zhang, Tongrui; Wang, Wuyang
Abstract: Form finding is one of the key issues in the design of spatial arch bridges. To address this issue, the present study proposes an iterative form-finding algorithm and establishes a corresponding numerical model. Geometric nonlinearity can be considered, and the only requirement is to determine the location of the arch foot and deck shape. To validate the applicability of the proposed algorithm, we adopt it for spatial arch 7bridges with various shapes. The parameters that influence the optimized form-finding results are systematically investigated. The influence of element size can be avoided through the proposed loading method. Results of this study indicate that the proposed algorithm is efficient and accurate for the design of spatial arch bridges.